The Search for Topographic Correlations within the Reiner Gamma Swirl - John R. Weirich; Deborah L. Domingue; Frank C. Chuang; Amanda A. Sickafoose; Matthew D. Richardson; Eric E. Palmer; Robert W. Gaskell (The Planetary Science Journal, 2023)
Lunar swirls have been traditionally considered to be unaffected by topographic changes. Yet, correlations between areas of high albedo and lower elevations are observed in regions of the Mare Ingenii swirl. Here, we apply similar techniques used at Mare Ingenii to determine if correlations between swirl units and topography also exist within Reiner Gamma. We generate topography using the techniques of stereophotoclinometry to Lunar Reconnaissance Orbiter Camera Narrow Angle Camera images to derive meter- to submeter-scale topography. We choose a 50 km ^2 study region with a 2.6 m ground sample distance (GSD), and within this region there is a 1 km ^2 subregion with a 0.8 m GSD. We use surface reflectance data at multiple viewing geometries to classify these regions into different swirl units using machine learning techniques. Statistical analyses of the data show mean height variations between on- and off-swirl of ∼4 m, with on-swirl at a lower elevation. It is not clear how this scale of elevation difference influences the formation of swirl units, but it supports postulations of dust migration and magnetic sorting contributing to their formation.